The Routledge history of emotions in the modern world
1 online resource.
Keywords: "The Routledge History of Emotions in the Modern World brings together a diverse array of scholars to offer an overview of the current and emerging scholarship of emotions in the modern world. Across thirty-six chapters, this work enters the field of emotion from a range of angles. The Routledge History of Emotions in the Modern World is the perfect resource for all students and scholars interested in the history of emotions across the world from 1700"--